Robust inactivation of Plasmodium falciparum in red blood cell concentrates using amustaline and glutathione pathogen reduction. Issue 5 (6th April 2022) - Sow, Cissé; Bouissou, Amélie; Girard, Yvette A.; Singh, Gurvani B.; Bounaadja, Lotfi; Payrat, Jean‐Marc; Haas, Delphine; Isola, Hervé; Lanteri, Marion C.; Bringmann, Peter; Grellier, Philippe
Abstract: Background: Plasmodium falciparum is the parasite responsible for most malaria cases globally. The risk of transfusion‐transmitted malaria (TTM) is mitigated by donor deferrals and blood screening strategies, which adversely impact blood availability. Previous studies showed robust inactivation of P. falciparum using nucleic acid‐targeting pathogen reduction technologies (PRT) for the treatment of plasma and platelet components or whole blood (WB). The efficacy of the amustaline–glutathione (GSH) PRT to inactivate P. falciparum is here evaluated in red blood cells (RBC), as well the impact of PRT on parasite loads, stages, and strains. Study Design and Methods: RBC units resuspended in AS‐1 or AS‐5 additive solutions were spiked with ring stage‐infected RBC and treated with the amustaline–GSH PRT. Parasite loads and viability were measured in samples at the time of contamination, and after treatment, using serial 10‐fold dilutions of the samples in RBC cultures maintained for up to 4 weeks. Results: P. falciparum viability assays allow for the detection of very low levels of parasite. Initial parasite titer was >5.2 log10 /ml in AS‐1/5 RBC. No infectious parasites were detected in amustaline–GSH‐treated samples after 4 weeks of culture. Amustaline–GSH inactivated high parasite loads regardless of parasite stages and strains. Amustaline readily penetrates the parasite, irreversibly blocks development, and leads to parasite death and expulsion from RBC. Discussion: Amustaline–GSH PRT demonstrated robust efficacy to inactivate malaria parasites in RBC concentrates. This study completes the portfolio of studies demonstrating the efficacy of nucleic acid‐targeting PRTs to mitigate TTM risks as previously reported for platelet concentrates, plasma, and WB.